2024
DOI: 10.5713/ab.23.0232
|View full text |Cite
|
Sign up to set email alerts
|

Replacing alfalfa hay with amaranth hay: effects on production performance, rumen fermentation, nutrient digestibility and antioxidant ability in dairy cow

Jian Ma,
Xue Fan,
Guoqing Sun
et al.

Abstract: Objective: The aim of this research was to explore the effects of dietary substitution of alfalfa hay by amaranth hay on production performance, rumen fermentation, nutrient digestibility, serum biochemical parameters and antioxidant ability in dairy cows.Methods: A total of 45 healthy Holstein cows with same parity and similar milk yield and body weight were randomly divided into 3 groups: control diet without amaranth hay (CON) or 50% and 100% alfalfa hay replaced by an equal amount of amaranth hay (dry matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Studies suggest that red amaranth is notably abundant in polyphenols, particularly found in the seed coat [45][46][47]. The varieties with a superior red color index, such as A. cruentus and A. hypochondriacus, are significant reservoirs of phenolic and polyphenolic compounds, showing enhanced antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that red amaranth is notably abundant in polyphenols, particularly found in the seed coat [45][46][47]. The varieties with a superior red color index, such as A. cruentus and A. hypochondriacus, are significant reservoirs of phenolic and polyphenolic compounds, showing enhanced antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Ruminal characteristics are largely affected by the composition of the diet, and it is reasonable to evaluate the feasibility of the RRTR diet based on rumen fermentation characteristics(Ma et al, 2024). Rumen pH is an important measurement for ruminants because it is associated with acidbase balance, especially for the survival of ruminal microbes.…”
mentioning
confidence: 99%